Political Strategy of Gerindra Party in 2017 Local Election of DKI Jakarta (Case Study: Anies Baswedan – Sandiaga Uno) - Aqil Rizaldi Gaudart; Sulistyowati . (Journal of Politic and Government Studies, 2018)
Gerindra is winning again and subvert the incumbent candidate for the second time in order to carrying his candidate in 2017 Local Election of DKI Jakarta. The problem formulation from this research is how Gerindra's political strategy in recruitment, strategic planning, and strategy execution.The purpose of this research is to know what kind of political strategies used by Gerindra in order to carrying its candidate, so they can win for the second time in 2017 Local Election of DKI Jakarta.The answers to the problem and purpose of research are done by using political strategy theory including SWOT Analysis, Campaign Strategy and Political Marketing which analyzed through descriptive qualitative methodology. Gerindra Party became the main object of this research.The result of this research is Gerindra is winning because of effective and right targeted political strategy, has a militant mass base, and assisted by solid coalition and volunteers. Making the carried candidate surpass the votes of its opponents.After winning this political contest, Gerindra recommended to make an evaluation for the party in the future and oversee their carried candidate to fit with his political promises.Keywords: local election, political party, political strategy